Continuous Cropping of Tussilago farfara L. Has a Significant Impact on the Yield and Quality of Its Flower Buds, and Physicochemical Properties and the Microbial Communities of Rhizosphere Soil - Zhenbin Huang; Xia Wang; Liangshuai Fan; Xiaojun Jin; Xiang Zhang; Hongyan Wang (Life)
Continuous cropping obstacles pose significant constraints and urgent challenges in the production of Tussilago farfara L. This experiment investigated the effects of consecutive cropping on T. farfara over periods of 1, 2, and 3 years. It assessed the yield and quality of T. farfara flower buds, in addition to the physicochemical properties of the rhizosphere soil. The microbial community in the rhizosphere was analyzed through 16S rDNA and ITS sequencing using Illumina Novaseq high-throughput sequencing technology, while also examining the correlations among these factors. The results reveal that as the duration of continuous cropping increases, the yield of T. farfara flower buds, along with the contents of extract, tussilagone, and total flavonoids, steadily decreased; soil pH, organic matter, available phosphorus, available potassium, alkaline nitrogen, and the activities of sucrose, catalase, and alkaline phosphatase markedly decreased. As the duration of consecutive cropping increases, the quantity and diversity of bacteria in the rhizosphere soil initially increase and then decrease, while the number of fungal species increases by 22.5%. Meanwhile, continuous cropping of T. farfara contributes to a gradual reduction in the relative abundance of beneficial genera such as Ralstonia, Nitrospira, and Trichoderma in the rhizosphere soil, while harmful genera such as Mortierella, Fusarium, and Tricharina accumulate significantly. Correlation analysis shows that changes in microbial communities notably influence the growth of T. farfara and soil quality. This study elucidates the impacts of continuous cropping on the yield and quality of T. farfara flower buds, soil physicochemical properties, and the microbial communities in the rhizosphere, providing a scientific basis for further research on continuous cropping barriers and the selection of beneficial microbial genera for the growth of T. farfara.